LITERATURE STUDY: THE DEVELOPMENT OF INCLUSIVE EDUCATION IN SOUTH KOREA, THAILAND, AND INDONESIA - Distiani Fitria Kusuma (UIN Raden Mas Said Surakarta, 2021)
This study is conducted to collect sufficient information about the development of inclusive education in three Asian countries; South Korea, Thailand, and Indonesia. The research method applied in this study is a literature study. This study collects several previous studies to answer the development of inclusive education in Asia. The development of inclusive education that relates to the early history of inclusive education to its current practices. Every child has the right to obtain a proper education. This right is protected by law in every country. One of the programs carried out to achieve Education for All is special or inclusive education. This education program is a strategy used to protect the rights of disabled students to obtain a proper education without discrimination. Several studies have shown the obstacles and developments experienced by inclusive education. Every country has its own obstacles and progress. This study is expected to be an insight to know how the development of inclusive education in South Korea, Thailand, and Indonesia